Low-temperature wear-resistant resin for optical film and preparation method of low-temperature wear-resistant resin
By preparing a low-temperature wear-resistant resin composed of resin monomer, photoinitiator, acrylic resin, oligomer and smoothing additive, the problem of weakening of the self-repair ability of the existing resin at low temperature is solved, and the high wear-resistant performance of the brightening optical bonding film under low temperature conditions is achieved.
Patent Information
- Application Number
- CN202411904039.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
AI Technical Summary
The self-repairing ability of existing resins is weakened when lower than room temperature, resulting in the brightening optical bonding film being easily scratched during stacking, handling and transportation, and lacking good wear resistance.
A low-temperature wear-resistant resin composed of resin monomer, photoinitiator, acrylic resin, oligomer and slip additive are provided. The resin is dispersed evenly in a dark environment and heated to 30-40°C, and finally obtained by filtration.
The low-temperature wear-resistant resin has faster self-repairing properties under low temperature conditions, significantly improving the wear resistance of the brightening optical bonding film, and reducing the risk of scratches during stacking, handling and transportation.
Smart Images

Figure CN119735750A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of screen polyester films and relates to a low-temperature wear-resistant resin for optical films and a preparation method thereof. Background Art
[0002] With the vigorous development of liquid crystal display technology, the requirements for high-definition, ultra-high-definition, and lightweight components, the optical film technology used in liquid crystal flat panel display devices has also made rapid progress, especially the brightening optical bonding film independently installed on the liquid crystal display device, which constitutes the backlight module of the liquid crystal display together with the backlight source, light guide plate, etc. It can maximize the use of incident light while brightening and homogenizing the light emitted by the backlight source, and transmit the light to the liquid crystal display screen more efficiently. However, during the stacking, handling, and transportation of the brightening optical bonding film, the upper and lower sheets move relative to each other and rub against each other, causing scratches. Therefore, wear resistance is an important indicator of the brightening optical bonding film in liquid crystal flat panel display devices. Wear resistance depends on the resin on the surface of the brightening optical bonding film. The existing resin has a certain self-healing ability at room temperature, but when it is below room temperature, the self-healing ability is weakened, so it is necessary to invent a wear-resistant resin. Summary of the invention
[0003] The purpose of the present invention is to solve the defects of the prior art. When stacking, handling and transporting the optical bonding film, the upper and lower sheets move relative to each other and rub against each other, which may cause scratches. The wear resistance depends on the resin on the surface of the brightening optical bonding film. The existing resin has a certain self-repairing ability at room temperature, but the self-repairing ability is weakened when it is lower than room temperature. To this end, the present invention provides a resin with good self-repairing ability at low temperatures.
[0004] In one aspect, the present invention provides a low-temperature wear-resistant resin for an optical film, which is prepared from the following components in parts by weight:
[0005] Disperse 25-30 parts of resin monomer and 1-3 parts of photoinitiator evenly in a dark environment, continue to add 15-20 parts of the first type of acrylic resin, 25-30 parts of the second type of acrylic resin and 5-10 parts of oligomer, heat to 30-40°C in a dark environment and disperse evenly, finally add 0.5-1 part of slip agent, heat to 30-40°C and continue to disperse evenly, and obtain low-temperature wear-resistant resin after filtration.
[0006] The resin monomer is ethoxylated bisphenol A diacrylate resin; the first type of acrylic resin is o-phenylphenoxyethyl acrylic resin or ethoxylated o-phenylphenoxyethyl acrylic resin; the second type of acrylic resin is phenol acrylic resin or ethoxylated phenol acrylic resin; the oligomer is polyurethane acrylic resin or epoxy acrylic resin.
[0007] Preferably, the initiator is 4-(phenylthio)phenyldiphenylsulfonium hexafluoroantimonate.
[0008] Preferably, the first type of acrylic resin is o-phenylphenoxyethyl acrylic resin.
[0009] Preferably, the second type of acrylic resin is phenol acrylic resin.
[0010] Preferably, the oligomer is polyurethane acrylic.
[0011] Preferably, the weight proportions of the components are: 30 parts of resin monomer, 3 parts of photoinitiator, 20 parts of first type acrylic resin, 30 parts of second type acrylic resin, 10 parts of oligomer, and 1 part of slip agent.
[0012] Preferably, the dispersion is carried out by stirring, and the preferred stirring speed is 500-2000 r / min; the time required for uniform dispersion is preferably 20 to 60 min, more preferably 30, 35, 40, 45, 50, 55, 60 min.
[0013] Preferably, the filtering refers to filtering the uniformly mixed solution through a 0.5 micron filter bag and a 0.1 micron filter element.
[0014] Another aspect of the present invention provides a use of the low-temperature wear-resistant resin in preparing an optical film.
[0015] Another aspect of the present invention provides an optical film comprising the low-temperature wear-resistant resin.
[0016] The present invention has the following beneficial effects:
[0017] The low-temperature wear-resistant resin for optical films of the present invention has relatively fast self-repairing performance under low temperature conditions, and can solve the problem of scratches caused by relative movement and relative friction of upper and lower sheets of brightening optical bonding films during stacking, handling and transportation. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The figure shows a schematic cross-sectional view of the prism of the upper prism layer of the POP laminating film of the present invention;
[0019] Figure 2 Shown is a schematic structural diagram of the upper prism layer of the POP laminating film of the present invention;
[0020] Figure 3 The figure shows a schematic diagram of the side projection structure of the prism peaks of the upper prism layer of the POP laminating film of the present invention;
[0021] Figure 4 Shown is a schematic structural diagram of the POP laminating film of the present invention. DETAILED DESCRIPTION
[0022] In order to further understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0023] The present invention provides a low-temperature wear-resistant resin for an optical film, which is prepared from the following components in parts by weight:
[0024] Disperse 25-30 parts of resin monomer and 1-3 parts of photoinitiator evenly in a dark environment, continue to add 15-20 parts of the first type of acrylic resin, 25-30 parts of the second type of acrylic resin and 5-10 parts of oligomer, heat to 30-40°C in a dark environment and disperse evenly, finally add 0.5-1 part of slip agent, heat to 30-40°C and continue to disperse evenly, and obtain low-temperature wear-resistant resin after filtration.
[0025] The resin monomer is ethoxylated bisphenol A diacrylate resin; the first type of acrylic resin is o-phenylphenoxyethyl acrylic resin or ethoxylated o-phenylphenoxyethyl acrylic resin; the second type of acrylic resin is phenol acrylic resin or ethoxylated phenol acrylic resin; the oligomer is polyurethane acrylic resin or epoxy acrylic resin.
[0026] In some preferred embodiments, the initiator is preferably 4-(phenylthio)phenyldiphenylsulfonium hexafluoroantimonate.
[0027] In some preferred embodiments, the first type of acrylic resin is preferably o-phenylphenoxyethyl acrylic resin.
[0028] In some preferred embodiments, the second type of acrylic resin is preferably phenol acrylic resin.
[0029] In some preferred embodiments, the oligomer is preferably polyurethane acrylic.
[0030] In some preferred embodiments, dispersion is carried out by stirring, and the preferred stirring speed is 500-2000 r / min; the time required for uniform dispersion is preferably 20 to 60 min, more preferably 30, 35, 40, 45, 50, 55, 60 min.
[0031] In some preferred embodiments, the filtration system specifically refers to filtering the uniformly mixed solution through a 0.5 micron filter bag and a 0.1 micron filter element.
[0032] The low-temperature wear-resistant resin of the present invention can be used as a surface coating of an optical film, and the optical film includes but is not limited to a POP laminating film, a DOP laminating film, and a MOP laminating film.
[0033] In some more preferred embodiments, the low-temperature wear-resistant resin of the present invention can be used as a micro-prismatic structure coating material on the surface of a POP laminating film.
[0034] The POP laminating film is divided into two layers, namely, a structural layer (lower prism layer) and an upper prism layer from bottom to top. Both the structural layer and the upper prism layer may include a PET base layer and a microstructure surface layer coated on the PET base layer. The structural surface of the structural layer (lower prism layer) and the bottom surface of the upper prism layer are bonded by a composite adhesive.
[0035] The present invention provides a special POP laminating film, wherein the prisms of the prism layer are arranged in columns, the prism pitch is 18 to 20 microns, and the prism height is 9 to 10 microns. Figure 1 As shown, the cross section of the prism is a triangular structure with an arc-shaped top. The angle corresponding to the arc at the top is 88° to 90°, and the diameter of the corresponding circle is 0.8 microns. Figure 2 As shown in the figure, the peak (prism peak) at the top of a single prism of the upper prism layer is composed of a number of hemispherical structures of different sizes arranged in a certain order, forming a special structure of staggered heights. The prism described in the present invention is specifically a columnar shape, and its cross section is a triangular shape with an arc-shaped top. Due to the different sizes of hemispherical structures, the top heights of the cross sections of different parts of the prism will be different. The prism peak structure is as follows: Figure 3 As shown, there are several small hemispherical structures distributed between every two large hemispherical structures; the span of each large hemispherical structure is 50 microns and the height is 5 microns; the span of each small hemispherical structure is 10 microns and the height is 1 micron; the spacing between each large hemispherical structure is 50 microns, and B=n*C, 5 is a positive integer, that is, 5 small hemispherical structures are set.
[0036] The structural layer is arranged in a row with prisms having a triangular cross section. The configuration of the structural layer is consistent with that of a common POP laminating film. In a specific embodiment of the present invention, the prism spacing of the structural layer is 18 to 20 microns and the height is 9 to 10 microns.
[0037] The preparation method of the POP laminating film of the present invention is as follows: coating a resin on a PET base layer with a coating thickness of 20 to 30 μm, rolling out a desired micro-prism structure, and then placing the film under 700 mW / cm 2 The upper prism layer is prepared by curing the upper prism layer under ultraviolet irradiation with a power of 10s. The bottom surface of the PET base layer of the upper prism layer is bonded to the structural surface of the commercially available structural layer by a composite adhesive to finally obtain the POP laminating film, the structure of which is as follows: Figure 4 shown.
[0038] Example 1
[0039] Add 25 parts of monomer ethoxylated bisphenol A diacrylate resin and 1 part of initiator 4-(phenylthio)phenyl diphenylsulfonium hexafluoroantimonate into a flask in sequence, disperse at high speed of 1200r / min in a dark environment, disperse for 30 minutes, then continue to add 15 parts of the first type of acrylic resin o-phenylphenoxyethyl acrylic resin, 25 parts of the second type of acrylic resin phenol acrylic resin and 5 parts of oligomer polyurethane acrylic, heat to 30-40°C in a dark environment and continue to disperse at high speed of 1200r / min, disperse for 30 minutes, finally add 0.5 parts of slip agent, heat to 30-40°C and continue to disperse at high speed of 1200r / min, disperse for 60 minutes. After filtering through the filtration system, a low-temperature wear-resistant resin is obtained.
[0040] Example 2
[0041] Add 30 parts of monomer ethoxylated bisphenol A diacrylate resin and 3 parts of initiator 4-(phenylthio)phenyl diphenylsulfonium hexafluoroantimonate into a flask in sequence, disperse at high speed of 1200r / min in a dark environment, disperse for 30 minutes, then continue to add 20 parts of the first type of acrylic resin o-phenylphenoxyethyl acrylic resin, 30 parts of the second type of acrylic resin phenol acrylic resin and 10 parts of oligomer polyurethane acrylic, heat to 30-40°C in a dark environment and continue to disperse at high speed of 1200r / min, disperse for 30 minutes, finally add 1 part of slip agent, heat to 30-40°C and continue to disperse at high speed of 1200r / min, disperse for 60 minutes. After filtering through the system, a low-temperature wear-resistant resin is obtained.
[0042] Example 3
[0043] Add 25 parts of monomer ethoxylated bisphenol A diacrylate resin and 3 parts of initiator 4-(phenylthio)phenyl diphenylsulfonium hexafluoroantimonate into a flask in sequence, disperse at high speed of 1200r / min in a dark environment, disperse for 30 minutes, then continue to add 20 parts of the first type of acrylic resin ethoxylated o-phenylphenoxyethyl acrylic resin, 25 parts of the second type of acrylic resin ethoxylated phenol acrylic resin and 10 parts of oligomer polyurethane acrylic, heat to 30-40°C in a dark environment and continue to disperse at high speed of 1200r / min for 30 minutes, finally add 0.5 parts of a slip agent, heat to 30-40°C and continue to disperse at high speed of 1200r / min for 60 minutes. After filtering through the filtration system, a low-temperature wear-resistant resin is obtained.
[0044] Comparative Example 1
[0045] Add 3 parts of initiator 4-(phenylthio)phenyl diphenylsulfonium hexafluoroantimonate into a flask and disperse at high speed of 1200r / min in a dark environment. After dispersing for 30 minutes, continue to add 35 parts of the first type of acrylic resin ethoxylated o-phenylphenoxyethyl acrylic resin, 35 parts of the second type of acrylic resin ethoxylated phenol acrylic resin and 10 parts of oligomer polyurethane acrylic acid. Heat to 30-40°C in a dark environment and continue to disperse at high speed of 1200r / min for 30 minutes. Finally, add 0.5 parts of a slip agent, heat to 30-40°C, continue to disperse at high speed of 1200r / min, and disperse for 60 minutes. After passing through the filtration system, a low-temperature wear-resistant resin is obtained.
[0046] Test example:
[0047] Referring to the preparation method of the POP laminating film of the present invention, different samples were prepared by using the preparation methods of Examples 1-3 and Comparative Example 1.
[0048] Test method:
[0049] 1) Place the prepared POP laminated film sample upside down on the polarizer and place the whole in an environment of 25℃ and low temperature -40℃ for 30 minutes; 2) Press a weight on the POP, then pull the POP to make it slide and rub on the polarizer, and pull it back and forth three times; 3) Use a strong flashlight to check whether there are scratches on the surface of the polarizer. If there are scratches, reduce the weight; if there are no scratches, continue to increase the weight until scratches appear.
[0050] The test results are shown in Table 1. The POP laminating film using the new structure and low-temperature wear-resistant resin as the material can significantly reduce the wear of the polarizer in the low-temperature environment of POP.
[0051] The test results are shown in Table 1.
[0052] Table 1
[0053]
[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For the technical personnel in this field, the present invention can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made to the present invention should be included in the protection scope of the present invention.
Claims
1. A low-temperature wear-resistant resin for optical film, characterized in that: It is prepared from the following components in parts by weight: Disperse 25-30 parts of resin monomer and 1-3 parts of photoinitiator evenly in a dark environment, continue to add 15-20 parts of the first type of acrylic resin, 25-30 parts of the second type of acrylic resin and 5-10 parts of oligomer, heat to 30-40°C in a dark environment and disperse evenly, finally add 0.5-1 part of slip agent, heat to 30-40°C and continue to disperse evenly, and obtain low-temperature wear-resistant resin after filtration. The resin monomer is ethoxylated bisphenol A diacrylate resin; the first type of acrylic resin is o-phenylphenoxyethyl acrylic resin or ethoxylated o-phenylphenoxyethyl acrylic resin; the second type of acrylic resin is phenol acrylic resin or ethoxylated phenol acrylic resin; the oligomer is polyurethane acrylic resin or epoxy acrylic resin.
2. The low-temperature wear-resistant resin according to claim 1, characterized in that: The initiator is preferably 4-(phenylthio)phenyldiphenylsulfonium hexafluoroantimonate.
3. The low-temperature wear-resistant resin according to claim 1, characterized in that: The first type of acrylic resin is o-phenylphenoxyethyl acrylic resin.
4. The low-temperature wear-resistant resin according to claim 1, characterized in that: The second type of acrylic resin is phenol acrylic resin.
5. The low-temperature wear-resistant resin according to claim 1, characterized in that: The oligomer is polyurethane acrylic.
6. The low-temperature wear-resistant resin according to claim 1, characterized in that: The weight proportions of the components are: 30 parts of resin monomer, 3 parts of photoinitiator, 20 parts of first type acrylic resin, 30 parts of second type acrylic resin, 10 parts of oligomer and 1 part of slip agent.
7. The low-temperature wear-resistant resin according to claim 1, characterized in that: The dispersion is carried out by stirring, and the preferred stirring speed is 500-2000 r / min; the time required for uniform dispersion is preferably 20 to 60 min, and more preferably 30, 35, 40, 45, 50, 55, 60 min.
8. The low-temperature wear-resistant resin according to claim 1, characterized in that: The filtering refers to filtering the uniformly mixed solution through a 0.5 micron filter bag and a 0.1 micron filter element.
9. Use of the low-temperature wear-resistant resin according to any one of claims 1 to 8 in preparing an optical film.
10. An optical film comprising the low-temperature wear-resistant resin according to any one of claims 1 to 8.